2021
DOI: 10.3390/pharmaceutics14010092
|View full text |Cite
|
Sign up to set email alerts
|

Packaging and Delivery of Asthma Therapeutics

Abstract: Asthma is a life-altering, chronic disease of heterogenous origin that features a complex interplay of immune and environmental signaling. Although very little progress has been made in prevention, diverse types of medications and delivery systems, including nanoscale systems, have been or are currently being developed to control airway inflammation and prevent exacerbations and fibrosis. These medications are delivered through mechanical methods, with various inhalers (with benefits and drawbacks) existing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…Moreover, due to expression of molecules closely linked to the pathogenesis and phenotype of specific disorders, exosomes represent a promising tool for early disease diagnosis and personalized therapy (Purghè et al, 2021). Exosomes are characterized by considerable stability in extracellular environment, because of the lipidic bilayer, suggesting their potential application, not only as biomarkers but also as therapeutics agents (Mathis et al, 2021;Kadota et al, 2016). Engineered exosomes showed low immunogenicity and toxicity and could be able to deliver both lipophilic and hydrophilic drugs, with a preserved activity, to target cells (Raimondo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, due to expression of molecules closely linked to the pathogenesis and phenotype of specific disorders, exosomes represent a promising tool for early disease diagnosis and personalized therapy (Purghè et al, 2021). Exosomes are characterized by considerable stability in extracellular environment, because of the lipidic bilayer, suggesting their potential application, not only as biomarkers but also as therapeutics agents (Mathis et al, 2021;Kadota et al, 2016). Engineered exosomes showed low immunogenicity and toxicity and could be able to deliver both lipophilic and hydrophilic drugs, with a preserved activity, to target cells (Raimondo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are characterized by considerable stability in extracellular environment, because of the lipidic bilayer, suggesting their potential application, not only as biomarkers but also as therapeutics agents ( Mathis et al, 2021 ; Kadota et al, 2016 ). Engineered exosomes showed low immunogenicity and toxicity and could be able to deliver both lipophilic and hydrophilic drugs, with a preserved activity, to target cells ( Raimondo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence showed that circERBB2 and circHIPK3 could sponge miR-98-5p and miR-326, respectively, and promoted the proliferation of ASMCs by targeting IGF1R and STIM1 ( Lin et al, 2020 ; Huang et al, 2021c ). Circ-0001359 could attenuate airway remodeling by targeting FoxO1-dependent M2-like macrophage activation, with sponging miR-183-5p ( Shang et al, 2020 ; Mathis et al, 2021 ) ( Table 4 ). At present, although there are many studies on the competitively sponging of circRNAs to miRNAs, the specific effect of these circRNAs on asthma is not completely clear.…”
Section: Ncrnas In the Regulation Of Childhood Asthmamentioning
confidence: 99%